Jumlah Sel pada Isolat Monosit Setelah Paparan Tunggal Radiasi Sinar X dari Radiografi Periapikal (The Total of Cells on The Isolated Monocytes After Single Exposure of X-Ray Radiation from Periapical Radiography) - Karina Ardiny; Supriyadi .; Sonny Subiyantoro (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Periapical radiography projection is one of the most frequently used in dentomaxilofacial radiographs. The radiation source used in periapical radiographs are X-ray of ionizing radiation. The use of ionizing radiation can cause harmful effects to the body, where one of it is to the blood cells. The aim of the study was to determine the effect of a single exposure of X-ray radiation from periapical radiograph towards the total of cells on isolated monocytes. The design of the study was the Post Test Only Control Group Design.This research was conducted in the Radiology Installation Bioscience and in the Laboratorium of the Jember University Dental Hospital. The research sample was isolated monocyte cells derived from human peripheral blood (dependent variable). The sample was divided in to 2 groups randomly (the control group and the treatment group). The sample size used for the research is 6 samples in each group. The treatment group was given a single exposure periapical radiography of X-ray radiation at a dose of 1.54 mGy (independent variable). The living cells on isolated of monocytes were observed and calculated using an inverted microscope with 400x magnification using a trypan blue staining. The results of research used the Independent T-test found a significant difference (p<0.05) between the control and treatment groups. The conclusion of the research was that decreasing (31,53%) in the total of cells in isolated monocytes after a single exposure of X-ray radiation from periapical radiography. Keywords: Monocyte, Periapical Radiograph, X-Ray Radiation